1999
DOI: 10.1103/physrevb.59.9362
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen isotope effect on the vibrational modes ofLa1xCaxMnO

Abstract: Raman-scattering experiments have been carried out on polycrystalline samples of La 0.65 Ca 0.35 Mn 16 O 3 and isotope-exchanged La 0.65 Ca 0.35 Mn 18 O 3 as a function of temperature. The most interesting feature in the spectra is a vibrational mode that occurs at a nominal frequency of 0 Ϸ230 cm Ϫ1 , which is assigned to an out-ofphase rotational mode that involves motion of the O͑1͒ atoms. The frequency of this phonon depends strongly on the Ca concentration and has been correlated with the strength of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
4
21
0
Order By: Relevance
“…While a tensile strain affects the lattice strongly. These sharp peaks in the 400 to 500 cm −1 range always appear together in the Raman spectra of LCMO 37,41,43,45,46 . Based on their similar behavior with the temperature and substrates in our case and the earlier reports in films and bulk samples 37,41 , we attribute these narrow peaks to the same symmetry.…”
Section: A Effect Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…While a tensile strain affects the lattice strongly. These sharp peaks in the 400 to 500 cm −1 range always appear together in the Raman spectra of LCMO 37,41,43,45,46 . Based on their similar behavior with the temperature and substrates in our case and the earlier reports in films and bulk samples 37,41 , we attribute these narrow peaks to the same symmetry.…”
Section: A Effect Of Temperaturementioning
confidence: 99%
“…The peak of ω 1 sharpens slightly below 220 K. As shown in the inset of Fig.2a, the magnetic phase transition can be observed clearly, the Curie Temperature (T C ) is about 220 K. The sharpening of ω 1 peak has been reported earlier by Podobedov et al 38 and attributed to the spin-lattice coupling in the spin-ordered FM state. Recently, another explanation of this narrowing of ω 1 , could be the increase of long range structural coherence due to the reduction of the dynamic JT distortion 37,45 .…”
Section: A Effect Of Temperaturementioning
confidence: 99%
“…Recent experiments on LaMnO 3 have revealed the presence of high-energy modes (∼ 1000cm −1 ) which have been attributed to the orbital excitations [17]. However, doped manganites being pseudo-cubic, Raman lines are extremely weak and broad [9][10][11][12][13]. The number of modes observed in doped manganites are very few; e.g., in La 0.7 Ca 0.3 MnO 3 there are five modes observed at low temperature at 70, 133, 235, 435, and 670cm −1 [11].…”
mentioning
confidence: 99%
“…There are many Raman studies on manganites in recent times covering both the vibrational [9][10][11][12][13] and electronic Raman scattering [14] across the metal-insulator transition. In a recent work on polycrystalline Pr 0.65 Ca 0.35 MnO 3 [15], temperature dependence of the modes at 475 and 610cm −1 was studied and the splitting of these modes below T CO was attributed to the folding of the Brillouin zone in the CO state.…”
mentioning
confidence: 99%
“…Recently, it was reported that a bottleneck spin relaxation takes place from the exchange-coupled M n 4C ion via the M n 3C Jahn-Teller ions to the lattice. 18 Recently, Irwin et al 19 reported on an oxygen isotope effect for the vibration modes. They discussed mainly the blue shift of the out-ofphase rotational mode (230 cm 1 ) and explained the shift by a mode that incorporates a double-exchange mechanism in the presence of an electron-phonon interaction.…”
Section: Introductionmentioning
confidence: 99%